Femocrats and ecorats: Women's policy machinery in Australia, Canada and New Zealand - Marian Sawer (United Nations Research Institute for Social Development (UNRISD), 1996)
This paper focuses on the institutionalization of gender concerns within international and national policy machineries. During the United Nations Decade for Women (1976-1985) most member states of the United Nations adopted some form of governmental machinery to ensure that all government activity was monitored for its impact on women. This paper provides case studies of women's policy machinery in Australia, Canada and New Zealand. The title derives from the uneasy relationship between feminist bureaucrats (femocrats) and a new generation of decision-makers guided by principles of "economic rationalism" (ecorats). The concern of femocrats for gender equity has come up against the belief of ecorats that public intervention in markets is counter-productive.
Keywords: 330